2014
DOI: 10.1111/jpi.12193
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents cell death and mitochondrial dysfunction via a SIRT1‐dependent mechanism during ischemic‐stroke in mice

Abstract: Silent information regulator 1 (SIRT1), a type of histone deacetylase, is a highly effective therapeutic target for protection against ischemia reperfusion (IR) injury (IRI). Previous studies showed that melatonin preserves SIRT1 expression in neuronal cells of newborn rats after hypoxia-ischemia. However, the definite role of SIRT1 in the protective effect of melatonin against cerebral IRI in adult has not been explored. In this study, the brain of adult mice was subjected to IRI. Prior to this procedure, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
145
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 216 publications
(159 citation statements)
references
References 56 publications
9
145
1
2
Order By: Relevance
“…All these findings suggested that the cardioprotective effect of Kae in cardiomyocytes subjected to A/R was related to mitochondrial pathway. The latest research shows that melatonin prevents cell death and mitochondrial dysfunction via a SIRT1-dependent mechanism during ischemic-stroke in mice (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…All these findings suggested that the cardioprotective effect of Kae in cardiomyocytes subjected to A/R was related to mitochondrial pathway. The latest research shows that melatonin prevents cell death and mitochondrial dysfunction via a SIRT1-dependent mechanism during ischemic-stroke in mice (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There were a few studies on the systemic administration of EX527 to mice, 44,45 and no adverse effect of EX527 was noted. Among the other inhibitors of SIRT1 and 2, an intravenous injection (twice a week for 4 weeks) of sirtinol (10 mg/kg) and a daily intraperitoneal injection of cambinol (100 mg/kg) did not induce weight loss or adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin confered cardioprotective effect against myocardial ischemia reperfusion injury by reducing oxidative stress damage via activation of SIRT1 signaling in a receptor-dependent manner . Melatonin treatment also attenuated cerebral ischemia-reperfusion injury in mice by reducing ischemia reperfusion-induced mitochondrial dysfunction through the activation of SIRT1 signaling and the attenuation of mitochondrial oxidative damage (Yang et al, 2015).…”
Section: Melatoninmentioning
confidence: 99%